Envisioning Media Power: On Capital and Geographies of Television - Christophers, Brett (Lexington Books, 2009)
Envisioning Media Power develops an original geographical perspective on the nature and exercise of power in the international television economy. It uses theories of political economy as the basis for a comparative empirical examination of the UK and New Zealand television markets, while closely considering these markets' respective relationships with the US market and its globally-influential media corporations. In fleshing out this geographical perspective, the book critically addresses the power to produce, reproduce, and extract profit from territorialized media markets. To understand such powers, the book examines processes of creation and dissemination of industry knowledge, structures of industry governance, and the locational characteristics of television's operational economy. Through its rigorous and creative combination of conceptual insights with empirical substance, Envisioning Media Power both illuminates the fabric of television's international space economy, and ultimately offers a unique theoretic argument - suggesting that power, knowledge and geography are inseparable not only from one another, but from the process of accumulation of media capital.